2007
DOI: 10.1128/aem.00360-07
|View full text |Cite
|
Sign up to set email alerts
|

EnterohemorrhagicEscherichia coliBiofilms Are Inhibited by 7-Hydroxyindole and Stimulated by Isatin

Abstract: Since indole is present at up to 500 M in the stationary phase and is an interspecies biofilm signal (J. Lee, A. Jayaraman, and T. K. Wood, BMC Microbiol. 7:42, 2007), we investigated hydroxyindoles as biofilm signals and found them also to be nontoxic interspecies biofilm signals for enterohemorrhagic Escherichia coli O157:H7 (EHEC), E. coli K-12, and Pseudomonas aeruginosa. The genetic basis of EHEC biofilm formation was also explored, and notably, virulence genes in biofilm cells were repressed compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
191
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 177 publications
(199 citation statements)
references
References 82 publications
3
191
0
5
Order By: Relevance
“…coli had increased transcript abundance of yqhD in biofilm-associated cells treated with isatin relative to planktonic cells also treated with isatin (Lee et al 2007). Isatin is an oxidized indole with two ketone groups and was being investigated due its role as a potential signaling molecule.…”
Section: E Coli Omics Data (University Of Oklahoma Gene Expression Dmentioning
confidence: 99%
“…coli had increased transcript abundance of yqhD in biofilm-associated cells treated with isatin relative to planktonic cells also treated with isatin (Lee et al 2007). Isatin is an oxidized indole with two ketone groups and was being investigated due its role as a potential signaling molecule.…”
Section: E Coli Omics Data (University Of Oklahoma Gene Expression Dmentioning
confidence: 99%
“…A series of genes including bssR/bssS, bhsA and ariR have been identified as regulating biofilm formation through indole (Domka et al, 2006;Lee et al, 2007c;Zhang et al, 2007), and hydroxy indoles have been shown to be signals for pathogenic E. coli Lee et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…In prokaryotes, isatin has been identified as a signaling molecule in biofilm formation and during chemotactic response. Biofilm formation by enterohemorrhagic Escherichia coli increased 4-fold when exposed to isatin (11). Cellular migration toward higher isatin concentration was observed when E. coli were subjected to isatin concentration gradients (12).…”
mentioning
confidence: 99%